2016
DOI: 10.1080/01490400.2015.1077178
|View full text |Cite
|
Sign up to set email alerts
|

A method for testing the effect of management interventions on the satisfaction and loyalty of national park visitors

Abstract: QUERY SHEETThis page lists questions we have about your paper. The numbers displayed at left can be found in the text of the paper for reference. In addition, please review your paper as a whole for correctness.Q1. Au: provide publisher location. TABLE OF CONTENTS LISTINGThe

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 34 publications
(142 reference statements)
0
9
0
Order By: Relevance
“…It has been suggested that providing services and facilities within protected areas strongly affects visitors' satisfaction and experiences (Taplin, Rodger, & Moore, 2016). There are pressures on most national parks worldwide to accommodate increasingly diverse activities and provide more facilities (Frost & Hall, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that providing services and facilities within protected areas strongly affects visitors' satisfaction and experiences (Taplin, Rodger, & Moore, 2016). There are pressures on most national parks worldwide to accommodate increasingly diverse activities and provide more facilities (Frost & Hall, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, SQ expectations are found to be relatively lower on the following attributes: (1) materials visually appealing, (2) facilities reflect local influence, (3) employees give personal attention and (4) employees give individual attention. Taplin et al (2016) conducted a randomized experiment to analyse the causal relationship between SQ and visitor satisfaction and loyalty in national parks using Yanchep National Park in Western Australia as a case study. They employed a three-part structured questionnaire: (1) trip characteristics; (2) importance and performance evaluation (worded as 'satisfaction' in the questionnaire) of nine SQ attributes using a seven-point Likert-type scale with 1 being the lowest (Not at all important/not at all satisfied) and 7 the highest (Extremely important/ extremely satisfied) and ( 3) three questions on overall visitor satisfaction and eight questions measuring the likelihood of loyalty behaviours.…”
Section: Literature Review On Sq In National Parksmentioning
confidence: 99%
“…The author needs to include the new dimension eco-tangible as some characteristics of the tourist products regarding ecotourism are more related to the conservation face of the binomial expressed above. Similarly, Lee et al (2004) and Taplin et al (2016) contend that SERVQUAL cannot be directly replicated in forests or national parks, and that specific adaptations of concepts are needed. Therefore, different lists of items have been adapted under distinct natural products.…”
Section: Literature Review On Sq In National Parksmentioning
confidence: 99%
See 1 more Smart Citation
“…Satisfaction is important because it is an indicator of the quality of leisure and education services provided to society. Moreover, satisfaction is essential to boost demand since it increases intention to revisit and recommend the NPA to friends and relatives (Lee, Graefe, and Burns 2004; Rodger, Taplin, and Moore 2015; Taplin, Rodger, and Moore 2016), and to make online positive reviews (Hosany et al 2016; Prayag et al 2015).…”
Section: Introductionmentioning
confidence: 99%